COMPUTER SCIENCE TEXTBOOKS FROM THE PERSPECTIVE OF TEACHERS - MALIŠŮ, Petri; ŠALOUN, Petr (Trends in education, 2021)
In today's world of digital technology, the question arises whether there is still a place for traditional paper textbooks, in particular in informatics-related subjects that are using mainly computers for teaching. This paper sums up early results of the research: "The usage of educational materials in informatics" focused on the role of textbooks in informatics. The research explored the following topics: whether teachers are using textbooks and how, what are the weak points of current textbooks and how teachers imagine an ideal computer science textbook.
Keywords: Textbooks; informatics education; educational materials